Imaging small animals with positron emission tomography - Schäfers, K. P. (Nuklearmedizin - NuclearMedicine, 2003)
During the past few years many research centers have successfully applied their knowledge of positron emission tomography (PET) to construct PET scanners which are dedicated to image small animals such as rats and mice. Although there are many in-house built systems which are used in laboratory environments, only a few of them are commercially available at this time. This review will give an overview of dedicated animal PET systems with their technical description and main physical characteristics. Graphical analysis of spatial resolution against absolute sensitivity allows a comparison of the most important characteristics of each camera.The quadHIDAC, a PET scanner recently installed at the Department of Nuclear Medicine, University Hospital Münster, acquires images with sub-millimeter spatial resolution. A 18F-FDG whole body image of a mouse with small structures like the left ventricle of the heart clearly visualized, demonstrates its excellent spatial resolution.
Keywords: Positron emission tomography; animal; molecular imaging